Estratégias de adesão ao tratamento da tuberculose por pessoas em situação de rua: scoping review - Gobbi, Drieli Rezende (Universidade Federal de São Carlos, 2020)
Brazil occupies the 18th position in absolute numbers of tuberculosis cases because concentrates 80% of the cases in the world. Tuberculosis is a contagious infectious disease multifactorial character, considered a public health problem, associated with social factors such as social exclusion, marginalization, precarious housing, malnutrition and difficult access to public health services. Studies estimate that one third of the world population is infected with the bacillus causing the disease. Advances in diagnosis, clinical management, treatment and follow-up strategies are not sufficient to eradicate the disease in the country. There are also some factors that make difficult to adhere to treatment, such as: poverty, ignorance of the disease, multidrug resistance and long time to complete treatment, co-infection with the human immunodeficiency virus (HIV), centralization of treatment in health services, lack of fixed residence, immigration and chemical dependency. The homeless population is 48 to 67 times more likely to fall ill with tuberculosis than the general population. There are few studies about the homeless population and tuberculosis and is known that is a population that needs a scientific look, due to its high incidence coefficient and abandonment of treatment. Data from the municipality of São Paulo recorded a proportion of treatment abandonment in 2014 of 40.5% in the homeless population. Thus, this study aims to systematize the knowledge produced about tuberculosis in the homeless population through scooping review. The searches were performed from October to November 2019 in the established electronic databases, by means of descriptors and synonyms. Fourteen studies were analyzed that met the established inclusion criteria and/or collaborated to answer the research question. Concluded that the homeless population has specific health needs, being the best strategies for adherence to tuberculosis treatment, flexibility, intersectorality and decentralization of services, establishment of attachment, training of the multiprofessional team to deal with homeless population, health education and development of public policies that take into account the needs of this population.
Strategies for adhering to tuberculosis treatment by homeless population: scoping review
Keywords: Tuberculose; População em situação de rua; Estratégia; Tuberculosis; Homeless population; Health resources; CIENCIAS DA SAUDE::ENFERMAGEM